2020
DOI: 10.1108/ilt-05-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a transverse crack on the dynamic behaviours of a 3D rod-fastening rotor bearing system

Abstract: Purpose This paper aims to examine the dynamic behaviours of a three-dimensional (3D) rod-fastening rotor bearing system (RFBS) with a crack in a fastening rod. Design/methodology/approach Based on the 3D finite element method model and stress analysis of a cracked RFBS, a 3D dynamic model of the RFBS with a crack in a fastening rod is established with considering the initial bending and stress redistribution caused by the crack. A combined numerical simulation technology is used to investigate the dynamic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Li et al [27] studied the nonlinear dynamic characteristics of a three-disk bending torsional coupling rod fastening rotor under rub impact fault, concluded that the influence of torsional vibration on bending vibration gradually increases with the increase in rotating speed. Wang et al [28,29] studied the dynamic characteristics of rod fastening rotor under the coupling fault state, which are the non-uniform contact stressors of the disks, crack, initial bending and others, and carried out experimental verification. Hei et al [30,31] studied the nonlinear dynamic characteristics of coupling faults, which are the rod fastening rotor with looseness of support and rub impact.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [27] studied the nonlinear dynamic characteristics of a three-disk bending torsional coupling rod fastening rotor under rub impact fault, concluded that the influence of torsional vibration on bending vibration gradually increases with the increase in rotating speed. Wang et al [28,29] studied the dynamic characteristics of rod fastening rotor under the coupling fault state, which are the non-uniform contact stressors of the disks, crack, initial bending and others, and carried out experimental verification. Hei et al [30,31] studied the nonlinear dynamic characteristics of coupling faults, which are the rod fastening rotor with looseness of support and rub impact.…”
Section: Introductionmentioning
confidence: 99%
“…e results show that the greater the rotating speed, the greater the influence of rub impact force on the rotor. Wang et al [14,15] studied the influence of coupling faults such as uneven contact stress distribution between two disk and initial bending of the system due to the existence of cracks on rotor dynamic characteristics and verified it through experiment. Cui et al [16] used finite element method to study the dynamic characteristics of rod fastening rotor under different preload and bearing assembly clearance.…”
Section: Introductionmentioning
confidence: 99%